PABRIK VINIL ASETAT DARI ETILEN DAN ASAM ASETAT KAPASITAS 25.000 TON/ TAHUN - , ARI SETIO NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Process producing vinyl acetate from ethylene and acetic acid takes place in fixed bed multitube reactor at non-isothermal non-adiabatic condition by using Palladium CTV-IVTM catalyst with 1,5 % Pd dan 0,8% Au, using silica granules as the supported material. The reaction occurs in the gas phase at temperature 150 oC and pressure 9 atm. The vinyl acetate plant with capacity 25,000 tonne/year will be located in Cilegon, Banten. It needs area 5 hectare and 210 employees. The plant needs main raw materials of ethylene 16,878.79 tonne/year and acetic acid 19,331.93 tonne/year. The utilities used include water at the rate of 275,747.9298 tonne/year gotten from Cidanauâs reservoir at Cilegon, Banten